In vitro iron-binding and iron uptake capacities of defatted rice bran peptide hydrolysate - Foong, Lian Chee (2016)
Iron deficiency anaemia (IDA) is a global public health problem affecting 24.8% of the world population with over 90% coming from developing countries. In Malaysia, a prevalence of 35% anaemia has been reported. Iron deficiency has been associated with serious physiological consequences as well as deleterious effects on economies. To overcome IDA, iron fortification in food was used as an alternative approach to improve iron bioavailability. In the present study, the functional properties of defatted rice bran (DRB) peptides were explored as potential iron-binding peptides to enhance iron uptake in human. The DRB is a by-product of oil extraction from rice bran by supercritical fluid extraction (SFE). SFE is a green technology and yield-promising extraction technique which has shown superiority in many aspects over traditional extraction methods including Soxhlet extraction. The present study showed that defatting of rice bran by SFE yielded similar protein contents as compared with other extraction methods; the maximum amount of protein was obtained over mild SFE conditions (450 bars, 90 min of extraction, and 17.5 g/min flow rate). The study revealed that SFE could be used for the extraction of oil from rice bran while conserving the protein content in defatted residues. Besides that, amino acid analysis of DRB showed that the amino acids in DRB were in sufficient quantity required for an adult (except methionine and cysteine) and met the amino acid score based on the reference protein of FAO/WHO/UHU. Bioactive peptides from DRB after treatment with food-based proteolytic enzymes exert better biological functions or physiological effects on the peptide itself. Therefore,the iron binding capacity of the DRB protein hydrolysates as affected by enzyme types and degree of hydrolysis (DH) were also studied. DRB hydrolysates produced by combination treatment of an endo-protease (Alcalase) and exo- protease (Flavourzyme) were found to have the best iron-binding capacity (83%) at the 90 min time of hydrolysis. Furthermore, iron cell retention, transport, and uptake from DRB peptide hydrolysates after digestion were investigated using in vitro digestion/Caco-2 cells model. Transport and uptake efficiency of DRB hydrolysates obtained using combined treatment of Alcalase and Flavourzyme were significantly higher than those of other DRB hydrolysates and DRB protein without enzymatic hydrolysis. The optimal hydrolysis time to produce the best iron-binding DRB hydrolysate using combination treatment of Alcalase and Flavourzyme was 180 min. Overall, the results support the application of iron-binding peptides from DRB processing by-products in food fortification product.